Case studies in language curriculum design : concepts and approaches in action around the world - Macalister, John (New York ; London : Routledge ; Taylor & Francis Group, 2011)
Case studies are a powerful pedagogical tool for illuminating constructs and models in real-life contexts. Covering a wide range of teaching-learning contexts and offering in-depth analyses of ESL/ELT language curriculum design issues, this casebook is distinctive and unique in that each case draws on and is clearly linked to a single model presented in Nation and Macalister$1 (Bs Language Curriculum Design (www.routledge.com/9780415806060), giving the book a high degree of coherence. A short commentary by the editors after each case highlights features of note and/or issues arising from it. This is a versatile text, designed to work as a companion to Language Curriculum Design (adding meaning and depth to the model presented there by relating it to a range of applications), as a stand-alone text, or as a resource for language teacher trainees, teacher educators, practicing teachers, program administrators, and materials writers in the field.s
1. Introduction -- 2. A survival language learning syllabus for foreign travel -- 3. Design meeting context: a general english course for Burmese adults -- 4. Designing english language courses for Omani students -- 5. My ideal vocabulary teaching course -- 6.Opening the door to international communication: Peruvian officials and APEC -- 7. Helping skilled migrants into employment: the workplace communication program -- 8. The blended language learning course in Taiwan : issues and challenges of instructional design -- 9. Designing the assessment of a university ESOL course -- 10. Refreshing a writing course: the role of evaluation -- 11. Localizing Spanish in the Ann Arbor languages partnership: developing and using a teachable curriculum -- 12. Learning to teach Spanish: identifying, inducting, and supporting apprentice teachers in the Ann Arbor Languages Partnership -- 13. Negotiated syllabuses: do you want to? -- 14. Enhancing consumerist literacy practices in an urbanizing community -- 15. The teacher as intermediary between national curriculum and classroom -- 16. Developing a blog writing program at a Japanese University.
Includes bibliographical references and index.
Keywords: ENGLISH LANGUAGE -- STUDY AND TEACHING -- FOREIGN SPEAKERS